2018
DOI: 10.3390/en11071900
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Analysis of Weather Forecast Data for Cooling Load Forecasting Based on the Monte Carlo Method

Abstract: Abstract:Recently, the cooling load forecasting for the short-term has received increasing attention in the field of heating, ventilation and air conditioning (HVAC), which is conducive to the HVAC system operation control. The load forecasting based on weather forecast data is an effective approach. The meteorological parameters are used as the key inputs of the prediction model, of which the accuracy has a great influence on the prediction loads. Obviously, there are errors between the weather forecast data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Regarding the load forecasts, Agüera et al [ 35 ] recommended the introduction of at least outdoor temperature forecasts, and they considered humidity estimations to be valuable. Studies that have accounted for weather forecasts have usually incorporated only outdoor temperature [ 52 ], outdoor temperature and relative humidity [ 34 , 36 ] or temperature and solar irradiation [ 32 ] but not all influential weather parameters. Previous studies from the authors have shown that weather parameters such as wind speed can be very influential on the building’s load [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the load forecasts, Agüera et al [ 35 ] recommended the introduction of at least outdoor temperature forecasts, and they considered humidity estimations to be valuable. Studies that have accounted for weather forecasts have usually incorporated only outdoor temperature [ 52 ], outdoor temperature and relative humidity [ 34 , 36 ] or temperature and solar irradiation [ 32 ] but not all influential weather parameters. Previous studies from the authors have shown that weather parameters such as wind speed can be very influential on the building’s load [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature recognizes the significant influence of the weather forecast on a building’s energy performance, especially outdoor temperature [ 32 ]. However, the impact of the uncertainty due to forecast weather data on building load forecasting is not well represented in the literature [ 33 , 34 , 35 ], and few studies have directly investigated its effect [ 31 , 32 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the energy demand between the real weather simulation and the simulations with each changed parameters through the mean (µ) and the standard deviation (σ), the significance of each weather parameter is obtained. Figure 7 shows, for this period of study, that the outdoor temperature is the most sensitive weather parameter and has the greatest impact on the energy demand, as other studies have concluded [25,52]. For this reason, in the following analysis, only the outdoor temperature will be used.…”
Section: Sensitivity Analysis Of Weather Parametersmentioning
confidence: 99%
“…There are many studies that highlight the importance of the weather files, measuring, for example, their impact on passive buildings [34], on micro-grids [35,36], etc., calculating the loads of district energy systems [37], the electricity consumption with demand response strategies [13], or evaluating the effect on comfort conditions [38]. Some analyzed the effect that certain parameters of the weather file have, emphasizing the temperature as the most sensitive value for load forecasting [39,40].…”
Section: Introductionmentioning
confidence: 99%